Kajika Frogs (Buergeria buergeri) as Premium Pets During the Japanese Modern Monarchical Period - Hoshina, Hideto (Ethnobiology Letters, 2020)
This study reviews articles about the prices of Kajika frogs (Buergeria buergeri) in eight Japanese newspapers published between 1884 and 1938. Frog prices have been converted to present-day United States dollars (US). The frogs had a wide range of prices. Premium individuals, in particular, were often sold for US1,000–2,000. In this paper, I discuss the reasons why exceptional individuals were traded at a high price in the market, although Kajika frogs were a common native species. Other topics, such as the presentation of frogs as gifts to royal families, are also discussed.